Pupillary block due to reverse implantation of a sulcus intraocular lens. Issue 3 (August 2016) - Zhang, Xuemin; Soni, Nishant; Alexander, Janet; Kalarn, Sachin; Saeedi, Osamah
Abstract : N/A: An 88‐year‐old woman with a history of complicated cataract extraction by phacoemulsification with sulcus intraocular lens (IOL) implantation developed pseudophakic pupillary block in the right eye after reverse implantation of the IOL. Postoperatively, the intraocular pressure (IOP) was persistently elevated. Chronic angle‐closure glaucoma was diagnosed and treated medically. The patient presented 5 years later with acute pupillary block. The diagnosis of reverse IOL implantation was confirmed by ultrasound biomicroscopy. Intraocular lens repositioning, anterior synechialysis, and Baerveldt tube shunt placement led to resolution of the pupillary block and well‐controlled IOP. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.